Investigation of the anti-inflammatory and anti-invasiveness effects of momordica balsamina leaf methanol extract using triple-negative breast cancer cell line MDA-MB-321 - Mohale, Tshwarelo Evidence (My University, 2023)
Cancer is the world's second leading cause of death, with current treatments accompanied by a myriad of undesirable side effects. Medicinal plants contain chemoprotective and more tolerable phytochemicals for cancer treatment, making them a better alternative to current cancer treatments. Thus, many indigenous plants have yet to be investigated for anticancer properties. In this study, the Momordica balsamina leaf methanol extract was evaluated for its potential anti-inflammatory and anti-invasiveness effects in interleukin-6-activated triple-negative MDA-MB-231 breast cancer cells. The dried ground leaves of M. balsamina were subjected to maceration in absolute methanol to obtain a crude M. balsamina leaf methanol extract. The Muse® cell count and viability assay was used to assess the effect of the M. balsamina leaf methanol extract on the viability of breast MDA-MB-231 and the kidney HEK-293 cells. The methanol extract induced a significant decrease in MDA-MB-231 and HEK-293 cell viability at 150 µg/mL and 125 µg/mL, respectively. The annexin-V-FLUOS assay was performed to determine the mode of cell death induced by the extract and to further confirm lack of significant cytotoxicity in MDA-MB-231 cells exposed to 75 or 100 µg/mL of the extract. The findings revealed that the reduction in extract-treated MDA-MB-231 cell viability was associated with a non-significant induction of apoptotic cell death. The assessment of the effect of the methanol extract on nitric oxide production using nitric oxide assay revealed that the extract induced nitric oxide production in IL-6-activated MDA-MB-231 cells. Wound healing and transwell cell invasion assays were employed to evaluate the effect of the methanol extract on the migration and invasiveness of IL-6-activated MDA-MB-231 cells, respectively. The results revealed that the methanol extract significantly inhibited the IL-6-induced migratory and invasive potential of IL-6-activated MDA-MB-231 cells. Western blot analysis showed that the methanol extract decreased MMP-2, MMP-9 and vimentin protein expression and increased TIMP-3 protein expression levels in IL-6-activated MDA-MB-231 cells. In addition, gelatin-zymography also showed that the methanol extract significantly decreased the proteolytic activity of MMP-2 and MMP-9 in IL-6activated MDA-MB-231 cells. Furthermore, an increase in Bax and decrease in Bcl-2, JAK2, STAT3, MMP-2 and MMP-9 mRNA expression, was observed in extract-treated IL-6-activated MDA-MB-231 cells as determined by quantitative reverse transcriptase xiv © University of Limpopo polymerase chain reaction (qRT-PCR). The adhesiveness of IL-6-activated MDA-MB231 cells to extracellular matrix (ECM) proteins was assessed using the cell adhesion assay and CHEMICON® ECM-cell adhesion array kit, respectively. The results showed that the methanol extract significantly inhibited the IL-6-induced MDA-MB-231 cell adhesiveness. This could be associated with the inhibition of the attachment of IL6-activated MDA-MB-231 cells to collagen I, II, IV, laminin, tenascin, fibronectin, and vitronectin. In conclusion, the M. balsamina leaf methanol extract inhibited the IL-6induced MDA-MB-231 cell invasiveness, migration, and adhesiveness through the modulation of the IL-6/JAK2/STAT3 pathway.
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2023
Keywords: Cancer; Indigenous plants; M. balsamina leaf; Breast; Medicinal plants; Breast -- Cancer -- Alternative treatment; Breast -- Diseases -- Diagnosis